1987
DOI: 10.1021/j100294a025
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation dynamics of metastable hydrogen ion clusters H5+, H7+, and H9+: experiment and theory

Abstract: Data are presented on the metastable H2 loss from H5+, D5+, H7 , and Hg+ ions formed in a high-pressure, temperature-variable ion source with coaxial electron beam, ion exit geometry. The metastable reactions occur in the second field free region of a reverse geometry mass spectrometer and require parent ion lifetimes of ~10-6 s. Substantial structure is observed in the kinetic energy distributions, derived from the metastaWe peak shapes, for Hs+, D5+, and H7+. Statistical theory modeling predicts a smooth P(E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…The experimental work on the hydrogen clusters has been concentrated on enthalpy variation measurements (∆H) [16,24,25,26,31,33] and collisional induced dissociation (CID) studies [34,35,36,37]. The ∆H measurements for the H + n clusters and for the most general X + (H 2 ) k clusters have been an important source of information about the cluster energetic properties and have guided the theoretical studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental work on the hydrogen clusters has been concentrated on enthalpy variation measurements (∆H) [16,24,25,26,31,33] and collisional induced dissociation (CID) studies [34,35,36,37]. The ∆H measurements for the H + n clusters and for the most general X + (H 2 ) k clusters have been an important source of information about the cluster energetic properties and have guided the theoretical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more attention has been dedicated to the H + 5 cluster. Its potential energy surface has been studied at high levels of calculation [13,14] and its presence in some interstellar environments in concentrations up two times higher than that of the H + 3 molecule has been investigated [15].Besides the H + 3 molecular ion, a large variety of atomic and molecular cations has been considered as a core for H 2 clustering: the first-column Li + , Na + and K + ions [16][17][18][19][20][21][22] Table I summarizes some properties of these X + (H 2 ) k hydrogen clusters.The experimental work on the hydrogen clusters has been concentrated on enthalpy variation measurements (∆H) [16,24,25,26,31,33] and collisional induced dissociation (CID) studies [34,35,36,37]. The ∆H measurements for the H + n clusters and for the most general X + (H 2 ) k clusters have been an important source of information about the cluster energetic properties and have guided the theoretical studies.…”
mentioning
confidence: 99%
“…Besides, we note that the proportion of D 2 in the H 2 gas of the source is less than 150 ppm. Moreover, it has been shown that deuterium appears mainly in even mass clusters [ 12]. Thus, the HD + pollution is negligeable (~10-5).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the single-collision conditions in the gas jet are also fulfilled for the double and triple production processes in the target thickness range x=<l.15 1014atoms/cm 2. This target thickness range corresponds to the dissociation of at the most 30% of the H + clusters in the gas jet [12] (a aiss= (28.8_+2.5) 10-16cm2). In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since both the even and odd clusters have similar binding energies 65 the lack of even-numbered cluster ions in most of the previous studies has been attributed to kinetic factors 66 related to the small nonreactive probability of the H 2 + ion core. 67 Recently, however, Tachikawa has speculated that H 4 + and H 6 + ions might exist at least in the solid if the excessive energy is rapidly and efficiently removed from the complexes.…”
Section: A Mass Spectramentioning
confidence: 99%